Completeness of intervention description in invasive cardiology trials: an observational study of ClinicalTrials.gov registry and corresponding publications - Lišnić, Viktoria; Ashraf, Hishaam; Viđak, Marin; Marušić, Ana (Frontiers in Medicine, 2023)
Introduction Non-pharmacological invasive interventions in cardiology are complex and often inadequately reported. Template for Intervention Description and Replication (TIDieR) checklist and guide were developed to aid reporting and assessment of non-pharmacological interventions. The aim of our study was to assess the completeness of describing invasive cardiology interventions in clinical trials at the level of trial registration and corresponding journal article publication. Methodology We searched for clinical trials in invasive cardiology registered in Clinicaltrials.gov and corresponding journal publications. We used the 10-item TIDieR checklist for registries and 12-item checklist for journal publications. Results Out of 7,017 registry items retrieved by our search, 301 items were included in the analysis. The search for corresponding published articles yielded 192 journal publications. The majority of trials were funded by the industry and were medical device trials. The median number of reported TIDieR items was 4.5 (95% CI 4.49–4.51) out of 10, and while the corresponding journal articles reported 6.5 (95% CI 6.0–6.5) out of 12 TIDieR items. Conclusion Registration and reporting of invasive cardiology trials is often incomplete and adequate detailed description of the interventions is not provided. TIDieR checklist is an important tool which should be used to ensure rigorous reporting of non-pharmacological interventions in cardiology.